3D printing of artificial skin patches with bioactive and optically active polymer materials for anti-infection and augmenting wound repair. Issue 1 (19th July 2021) - Zhao, Hao; Xu, Jingwen; Yuan, Haitao; Zhang, Endong; Dai, Nan; Gao, Zhiqiang; Huang, Yiming; Lv, Fengting; Liu, Libing; Gu, Qi; Wang, Shu
Abstract : A printable ink composed of a photoactive cationic conjugated polymer (PPV) and gelatin/alginate/hyaluronic acid was developed for 3D printing artificial skin patches with the biofunctions of anti-infection and augmenting wound repair. Abstract : A printable ink composed of a photoactive cationic conjugated poly(phenylene vinylene) derivative (PPV) and gelatin/alginate/hyaluronic acid is developed for 3D printing artificial skin patches. This patch shows excellent photodynamic therapy-based anti-infection superiority and outstanding bioactivity to facilitate wound repair. This study contributes to design new conjugated polymer inks for manufacturing functional skin patches.